Flowering and Growth Responses of Cultivated Lentil and Wild Lens Germplasm toward the Differences in Red to Far-Red Ratio and Photosynthetically Active Radiation - Yuan, Hai Y.; Saha, Shyamali; Vandenberg, Albert; Bett, Kirstin E. (Frontiers in Plant Science, 2017)
Understanding environmental responses of pulse crop species and their wild relatives will play an important role in developing genetic strategies for crop improvement in response to changes in climate. This study examined how cultivated lentil and wild Lens germplasm responded to different light environments, specifically differences in red/far-red ratio (R/FR) and photosynthetically active radiation (PAR). Three genotypes of each the seven Lens species were grown in environmentally controlled growth chambers equipped to provide light treatments consisting of different R/FR ratios and PAR values. Our results showed that overall, days to flower of Lens genotypes were mainly influenced by the R/FR induced light quality change but not by the PAR related light intensity change. The cultivated lentil (L. culinaris) showed consistent, accelerated flowering in response to the low R/FR light environment together with three wild lentil genotypes (L. orientalis IG 72611, L. tomentosus IG 72830, and L. ervoides IG 72815) while most wild lentil genotypes had reduced responses and flowering time was not significantly affected. The longest shoot length, longest internode length, and largest leaflet area were observed under the low R/FR low PAR environment for both cultivated and wild lentils. The distinctly different responses between flowering time and elongation under low R/FR conditions among wild Lens genotypes suggests discrete pathways controlling flowering and elongation, which are both components of shade avoidance responses. The yield and above-ground biomass of Lens genotypes were the highest under high R/FR high PAR conditions, intermediate under low R/FR low PAR conditions, and lowest under high R/FR low PAR light conditions. Three L. lamottei genotypes (IG 110809, IG 110810, and IG 110813) and one L. ervoides genotype (IG 72646) were less sensitive in their time to flower responses while maintaining similar yield, biomass, and harvest index across all three light environments; these are indications of better adaptability toward changes in light environment.